Mechanisms to Overcome Negative Social Identity and Legitimyze the System and the Stigma in the “El Castillo” Community, La Pintana, Chile - Cavieres Higuera, Héctor; Cheyre Triat, Manuel José (Geografares, 2017)
The present research explored the use of negative social identity coping mechanisms by the inhabitants of the El Castillo community in Santiago, Chile. The implications of such mechanisms to the legitimation of the social order are also analyzed. Methodologically this is an exploratory study based in open interviews, which were analyzed from the “social discourse analysis” approach. Findings show the existence of individual and cognitive mechanisms that legitimize the stereotypes of being criminals and drugdealers; also a dichotomous vision is produced regarding the inhabitants of the comunity that is based on the premise of “choice” or their rootlessness with the territory.Keywords: negative social identity, stigma, system justification.